1999
DOI: 10.1002/(sici)1099-1166(199912)14:12<1050::aid-gps56>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors accelerating cerebral degenerative changes, cognitive decline and dementia

Abstract: Objectives Factors accelerating cerebral degenerative changes represent potentially modifiable risks for cognitive decline. Putative risk factors accelerating subtle cognitive decline and dementia were correlated with repeated measures of cerebral atrophy, CT densitometry, perfusions and cognitive testing among neurologically and cognitively normative ageing volunteers. Methods Two hundred and twenty‐four normative subjects at increased risk for cognitive decline were admitted to the study. Mean entry age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 52 publications
6
74
0
2
Order By: Relevance
“…Although some studies point to a possible causal relationship with dementia [30][31][32][33], others challenge this point of view [34]. Shrinkage and atrophy of the brain are generally considered to be a risk factor for cognitive decline [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies point to a possible causal relationship with dementia [30][31][32][33], others challenge this point of view [34]. Shrinkage and atrophy of the brain are generally considered to be a risk factor for cognitive decline [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to greater brain morphological abnormalities, chronic cigarette smoking among individuals with AUD appears to modulate neurocognition. In general, brain shrinkage is a risk factor for cognitive decline and memory impairment in the elderly (e.g., Meyer et al, 1999;Visser et al, 1999), and, if occurring in middle age, may increase the risk for earlier and more rapid cognitive decline with advancing age.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using magnetic resonance imaging (MRI) scans, Gur et al (1991) observed that brain atrophy as indicated by increased cerebrospinal fluid volume with age was greater in males than in females; Cowell et al (1994) found greater age-related reductions in brain volume for both frontal and temporal lobes in males than in females; and Pruessner, Collins, Pruessner and Evans (2001) found a reduction in hippocampal volume across early adulthood for males but not for females. From such findings, it would be predicted that corresponding age by gender interactions would be found in behavioral data and, indeed, greater age-related cognitive decline in males than in females has been observed in both cross-sectional and longitudinal studies (e.g., Barrett-Connor & Kritz-Silverstein, 1999;Larrabee & Crook, 1993;Meyer et al, 1999;Rowe, Turcotte, & Hasher, 2004;Wiederholt et al, 1993;Zelinski & Stewart, 1998). Interestingly, similar results have been found in two studies of spatial memory in rhesus monkeys (Lacreuse et al, 2005;Lacreuse, Herndon, Killiany, Rosene, & Moss, 1999), suggesting that biological rather than sociocultural factors may underlie the gender differences in age-related decline.…”
Section: Introductionmentioning
confidence: 95%